Upaya Dinas Perindustrian dan Perdagangan Dalam Pemberdayaan Sumber Daya Insani di Industri Kecil Menengah Batik Jombang - Fachruddin, Andy (Universitas Negeri Surabaya, 2021)
Abstract This research is focused on discussing the efforts of the Department of Industry and Trade in Empowering Human Resources in the Batik Small and Medium Industry in Jombang. In Islam helping each other is a very noble work which is recommended in terms of goodness. This is also applied in the efforts of the Jombang local government to empower human resources. Researchers use the basic values of Islamic business ethics as a reference for measuring the application of justice, balance, accountability, morals, honesty, fulfillment of trust, intelligence, transparency, independence and freedom (responsibility, fairness), management, leadership, supervision. Through a qualitative approach, there are problems that must be answered, namely how the efforts of the Department of Trade and Industry in implementing human resource management empowerment for the small and medium batik industry in Jombang when examined in Islamic economics So that researchers can collect three components, namely data reduction, data presentation, and data verification. The results of the study indicate that the Jombang District Industry and Trade Office has not implemented the empowerment of Islamic small and medium-sized batik industry human resources because it still raises and passes animal batik motifs such as animal heads and management that is less Islamic, with this approach to the principles of transparency. , Accountability, Responsibility, Independency, Fairness.